2019
DOI: 10.3390/rs11161846
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Xinmo (China) Landslide Based on Interferometric Synthetic Aperture Radar Observation and Modeling

Abstract: The Xinmo landslide occurred on 24 June 2017 and caused huge casualties and property losses. As characteristics of spatiotemporal pre-collapse deformation are a prerequisite for further understanding the collapse mechanism, in this study we applied the interferometric synthetic aperture radar (InSAR) technique to recover the pre-collapse deformation, which was further modeled to reveal the mechanism of the Xinmo landslide. Archived SAR data, including 44 Sentinel-1 A/B data and 20 Envisat/ASAR data, were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…It should be noted that the acceleration started in April 2017 in [29], [32]. A sliding acceleration was revealed before the landslide event [30], and an abrupt acceleration after May 2017 was detected [31]. Those studies and ours identified similar accelerated patterns before the landslide event.…”
Section: (A)]supporting
confidence: 78%
“…It should be noted that the acceleration started in April 2017 in [29], [32]. A sliding acceleration was revealed before the landslide event [30], and an abrupt acceleration after May 2017 was detected [31]. Those studies and ours identified similar accelerated patterns before the landslide event.…”
Section: (A)]supporting
confidence: 78%
“…The geometry and slip distribution of the potential sliding plane were retrieved by modelling the InSAR-derived ground displacements and assuming shear dislocation on a planar source embedded in an elastic and homogeneous half-space (Okada, 1992). This analytical approach is widely applied to infer the source geometry of a seismogenic fault after an earthquake (Albano et al, 2017;Polcari et al, 2018;Stramondo et al, 2016), and several publications have shown its effectiveness in modelling of non-catastrophic sliding phenomena involving deep sub-planar sliding surfaces (Aryal et al, 2015;Kang et al, 2019;Moro et al, 2011). This is possible by introducing corrections that modify the simple half-space to include the local topography, allowing the sliding surface to lie above the zero-level half-space surface (Williams and Wadge, 1998).…”
Section: Estimation Of the Geometry And Slip Distribution Of The Pote...mentioning
confidence: 99%
“…Xiaoba landslide took place in Guizhou Province, China, whose front is a locking section of dolomite, and the obvious stress concentration and plastic deformation on the locking masses in the front of the landslide were found by Lin et al (2018). Based on the spatial-temporal deformation characteristics of the Xinmo landslide, Kang et al (2019) found the bulge reduction of the sliding surface and inferred that the locking masses should lie in the front of the landslide. Two landslides happened on the right bank of the Jinsha River in Baige Village, China, blocking the river; as discovered in eld surveys, shear surfaces were distinctly visible in the anti-sliding areas in the front of the Baige landslide (Deng et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On August 27, 2014, a similar large-scale landslide with one locking segment at its front toe occurred in Fuquan County, Guizhou province, China, which killed 23 people and destroyed 77 houses (Lin et al 2018). On June 24, 2017, a catastrophic landslide with locking masses in the front was triggered above the Xinmo Village, Maoxian County, Sichuan Province, China; it buried the whole Xinmo village (10 deaths, 73 people missing) and the sliding mass blocked over a distance of 1,300 m of the Songping River (Kang et al 2019; Wang et al 2019a).…”
Section: Introductionmentioning
confidence: 99%